Integration of STEM-PjBL on Alternative Energy Sources to Improve Entrepreneurial Science Thinking - Rusman, Rusman; Supriyadi, Supriyadi; Sulhadi, Sulhadi (Universitas Negeri Semarang, 2021)
The demographic bonus by 2030 requires everyone to compete for jobs. Cultivating character and entrepreneurial thinking is an alternative to dealing with limited employment opportunities. This study aims investigate the increase of entrepreneurial science thinking through the STEM-PjBL integration learning model on alternative energy sources. This study used the Mix Method method in the form of a Sequential Explanatory design that used quantitative data as the main data, while qualitative data as supporting data. From the resulted of observations on four aspects of entrepreneurial science thinking, all aspects have a percentage above 70% so that they are included in the criteria quite well. The results of these observations indicated that the research carried out is in accordance with the research objective, namely the integration of STEM-PjBL can improve entrepreneurial science thinking.